Ocenjevanja vedenja v šoli z vidika pedagoške teorije in prakse - Pšunder, Mateja (Sodobna pedagogika, 2008)
Recently, there have been many discussions about the educational role of public schools. The focus is mostly on the search for answers to the question how to increase the educational role of school. There are different views regarding this question. About a year ago there was a deep resounding to the suggestion of the association "Pobuda za šolo po meri človeka" (The initiative for a school suited to a man) to reintroduce assessing school behaviour into schools, which should increase the educational role of schools. We considered the suggestion as a challenge, therefore we decided to study how these themes were treated in the pedagogical theory and what direct participants of educational process - teachers thought about it. The experience from practice reveals that despite the fact that assessing behaviour was abolished more than a decade ago, teachers would still like to assess behaviour at school. The research proved that more than three quarters of teachers want to reintroduce assessing behaviour at school, which, according to their opinion, would have a positive influence mostly on pupils' behaviour. In addition, the research revealed also teachers' attitudes to the educational role of schools, their power and powerlessness respectively, when dealing with educational problems, difficulty in educational activities at the present time and the need of school co-operation with the environment, especially with parents.
Keywords: vzgoja in izobraževanje; osnovne šole; disciplina; vedenje; ocenjevanje vedenja; vzgojni koncepti